The Role of Lobbying in Shaping US Foreign Policy : Case Study of the American-Jewish lobby and the Palestinian Crises during the American President Donald Trump’s Service(2016-2020) - Akichi, Badr Eddine; Nebeg, Raouf, (University of Ammar Theledji -Laghouat, 2022)
Interest groups and lobbyists are widely regarded as the most important link between people and their governments, influencing their activities as well as being influenced by their pressure. The current dissertation examines the influence and capacity of interest groups and lobbies to share foreign policy results in the modern era, especially in the context of the Palestinian-Israeli conflict. Moreover, it is highly important to examine the Jewish lobby's influence and position in shaping US foreign policy, especially in the Middle East, during Donald Trump's administration (2016-2020). To provide a clear reason for the interest groups and lobby’s tremendous influence on US foreign policy, the American Jewish lobby and the Palestinian crisis is taken as a case study. The dissertation digs deep into the structure of the Jewish lobby and the strategies used by its founders to exert influence and shape policy within the White House. More specifically, this thesis examines the effect of the Jewish lobby on the Trump administration's foreign policy against the Middle Eastern and North African nations, including Palestine, Egypt, Morocco, Tunisia, and others. Finally, the current study clarifies how the American-Jewish lobby influenced the Trump administration's foreign policy towards the Palestinian-Israeli conflict